2020
DOI: 10.7861/clinmed.2019-0156
|View full text |Cite
|
Sign up to set email alerts
|

Integrating mental and physical health assessment in a neuro-otology clinic: feasibility, acceptability, associations and prevalence of common mental health disorders

Abstract: People with persistent physical symptoms are at risk of psychological symptoms, although recognition in medical settings is low. This is a retrospective observational study of 954 patients in a hospital outpatient neuro-otology clinic in order to assess the feasibility and acceptability of an electronic informatics system for collection of patient-reported outcomes, with real-time feedback to guide clinical care and describe the prevalence of anxiety and depressive symptoms. The proportion of patients successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…Psychiatric comorbidities are present in around 30-50% of the patients suffering from dizziness or vertigo. Among them, one of the most common ones were de ned as depression [5], with a prevalence of 4-62%, based on the literature [6]. Due to vertigo or dizziness, impaired QoL often occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Psychiatric comorbidities are present in around 30-50% of the patients suffering from dizziness or vertigo. Among them, one of the most common ones were de ned as depression [5], with a prevalence of 4-62%, based on the literature [6]. Due to vertigo or dizziness, impaired QoL often occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the limited number of studies (Herdman et al, 2020;Taylor et al, 2007) which examined the point/month prevalence of STBs among physiotherapy clients, a tentative estimate of 5.4% can be made, which although not directly comparable, is higher than the 12-month prevalence of suicidal ideation in Australia, which is 2.4% among the general population (Australian Government Department of Health, 2009). Potter et al (2003) found that 62% of physiotherapists see 41-80 clients per week.…”
Section: Discussionmentioning
confidence: 99%
“…Potter et al (2003) found that 62% of physiotherapists see 41-80 clients per week. Using the figures from three studies (Herdman et al, 2020;Potter et al, 2003;Taylor et al, 2007), it could be estimated that physiotherapists may encounter between two and five clients with STBs per week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of handicap does not necessarily correlate with deficits on neuro-otological tests measuring the structural integrity of peripheral or central vestibular systems ( 12 14 ). In contrast, studies have shown strong correlations between the DHI and anxiety, depression, and autonomic arousal ( 15 21 ) and pathophysiological mechanisms have been proposed to explain this ( 22 ). Patients with prior anxiety and neurotic personality traits may also be more likely to develop secondary functional disorders such as “persistent postural perceptual dizziness” ( 23 ).…”
Section: Introductionmentioning
confidence: 94%